Legendary landscapes: a cultural geography of the Paul Bunyan and Blue Ox phenomena of the North woods - Harty, John Patrick (Kansas State University, 2007)
Landscapes express much of who we are. Our history, thoughts, and values are all interwoven into cultural landscape features. By researching the landscape similarities and dissimilarities on the regional level, geographers are able to learn more about a people's identity. Scattered across the vast expanses of the Northwoods, residents and visitors alike are greeted by representations of a lumberjack and his blue ox. In addition to large statues of Paul Bunyan and the Blue Ox, festivals, sporting events, businesses, and public lands are all named in honor of the two folk giants. These features are so prevalent and well known that references to the region by those who live outside the Northwoods often begin by acknowledging the folk heroes. This study explains the relationship between Paul Bunyan and the Northwoods region. Focusing on the area of northern Minnesota between the towns of Bemidji and Brainerd, qualitative research methods were conducted over a four-year period (2004-2007) to better understand the phenomena. Since the 1930s, residents of the Northwoods have used Paul Bunyan and Babe the Blue Ox landscape features to celebrate symbolically the region’s golden age of logging. These representations have evolved over the years to include both public and private landscape features. Given the level of permanence of many of the items as well as the authenticity, popularity, and attachment local residents express towards Paul and Babe, cultural landscape features of the lumberjack and his blue ox will continue to be seen as an integral component of the Northwoods regional identity.
Keywords: Paul Bunyan; Blue Ox; North woods; landscape; Region; Cultural Geography; Geography (0366)